2022
DOI: 10.1136/bmjopen-2021-053455
|View full text |Cite
|
Sign up to set email alerts
|

Approaches and outcomes of community health worker’s interventions for hypertension management and control in low-income and middle-income countries: systematic review

Abstract: ObjectivesTo critically appraise the scope, content and outcomes of community health worker (CHW) interventions designed to reduce blood pressure (BP) in low-income and middle-income countries (LMICs).MethodWe performed a database search (PUBMED, EMBASE, CINAHL, PsycINFO, OpenGrey, Cochrane Central Trials Register and Cochrane Database of Systematic Reviews) to identify studies in LMICs from 2000 to 2020. Eligible studies were interventional studies published in English and reporting CHW interventions for mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Positive interventions incorporating community health workers in low- and middle-income countries have focused mainly on behavior change for promoting BP control. 24 Residents in rural China who were randomized to a large-scale intervention involving trained village doctors saw significant improvements in BP control compared with enhanced usual care. 63 These providers initiated and titrated medications according to a standardized protocol under medical supervision and provided patient coaching.…”
Section: Key Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive interventions incorporating community health workers in low- and middle-income countries have focused mainly on behavior change for promoting BP control. 24 Residents in rural China who were randomized to a large-scale intervention involving trained village doctors saw significant improvements in BP control compared with enhanced usual care. 63 These providers initiated and titrated medications according to a standardized protocol under medical supervision and provided patient coaching.…”
Section: Key Challengesmentioning
confidence: 99%
“…[21][22][23] Community health worker interventions have also been associated with enhanced home BP monitoring, improvements in control, linkage to care, treatment adherence, and overall cardiovascular risk reduction in low-and middle-income settings. [24][25][26][27]…”
Section: Forerunner Solutions To Complete Remote Managementmentioning
confidence: 99%
“…4,5 CHWs can be vital in the effort to improve BP though a variety of actions complimentary to traditional healthcare professionals including culturally sensitive health coaching and education, improving engagement, trust and adherence, as well as addressing social-economic issues. 2,4,5 While their effectiveness has been most well established in recent studies among resource-constrained countries, 5 history shows that CHWs have long been involved in hypertension research in the United States as well. An analysis of 14 trials conducted between 1983 and 2005 6 and a review of more recent studies (n=5; 2010-2020) 4 both concluded that CHWs hold significant promise for improving BP control.…”
Section: See Article By Islam Et Almentioning
confidence: 99%
“…A key new team member in this model is the community health worker (CHW). 4,5 CHWs can be vital in the effort to improve BP though a variety of actions complimentary to traditional healthcare professionals including culturally sensitive health coaching and education, improving engagement, trust and adherence, as well as addressing social-economic issues. 2,4,5 While their effectiveness has been most well established in recent studies among resource-constrained countries, 5 history shows that CHWs have long been involved in hypertension research in the United States as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation